2016
DOI: 10.1007/s10803-016-2702-z
|View full text |Cite
|
Sign up to set email alerts
|

Increasing Responsive Parent–Child Interactions and Joint Engagement: Comparing the Influence of Parent-Mediated Intervention and Parent Psychoeducation

Abstract: Enhancing immediate and contingent responding by caregivers to children’s signals is an important strategy to support social interactions between caregivers and their children with autism. Yet, there has been limited examination of parents’ responsive behaviour in association with children’s social behaviour post caregiver-mediated intervention. Eighty-five dyads were randomized to one of two 10-week caregiver-training interventions. Parent–child play interactions were coded for parental responsivity and child… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
57
0
3

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 93 publications
(63 citation statements)
references
References 35 publications
(65 reference statements)
3
57
0
3
Order By: Relevance
“…While many parents benefit from coaching in implementation of child-responsive strategies, some are slow adopters (Schertz & Odom, 2007; Shire, Gulsrud, & Kasari, 2016). This could be due to a number of factors.…”
Section: Naturalistic Developmental Behavioural Intervention (Ndbi) Amentioning
confidence: 99%
See 1 more Smart Citation
“…While many parents benefit from coaching in implementation of child-responsive strategies, some are slow adopters (Schertz & Odom, 2007; Shire, Gulsrud, & Kasari, 2016). This could be due to a number of factors.…”
Section: Naturalistic Developmental Behavioural Intervention (Ndbi) Amentioning
confidence: 99%
“…Eldevik et al, 2010; Magiati, Charman, & Howlin, 2007; Virués-Ortega, Rodriguez, & Yu, 2013). Related to dosage is fidelity of implementation, which is associated with improved child behaviour and reduced parent stress (Aldred et al, 2004; Shire et al, 2016; Strauss et al, 2012). Some researchers did not identify dosage effects, but instead reported that interventionist characteristics (e.g.…”
Section: Predictors Of Positive Child Outcomesmentioning
confidence: 99%
“…Exploratory analyses also examined whether caregivers were more successful in their responses to child RRBs following intervention. Our hypotheses were based on the prior findings of Gulsrud, Hellemann, Shire, and Kasari [], Kasari et al [], and Shire, Gulsrud, and Kasari [] who all report data from this sample. Kasari et al [] found increases in joint engagement, play diversity, and play level.…”
Section: Current Study: Rationale and Hypothesesmentioning
confidence: 99%
“…In this respect our discovery of a substantial relationship between maternal responsivity and the VABS communication domain is further verification of our earlier findings. More generally, maternal responsivity has been repeatedly shown to be among the most potent environmental influences on a variety of child development measures across both typically and atypically developing children (Landry et al, 2006, 2001; Spiker et al, 2002; Warren & Brady, 2007; Shire et al, 2016). Furthermore, our findings regarding the influence of contingent maternal responsivity on child adaptive behavior underscores the fact that the manifestation of FXS is not just the product of innate biology, but is attributable to the dynamic and cumulative interaction of biology, behavior, and environment over time.…”
Section: Discussionmentioning
confidence: 99%